PENINGKATAN KOMPETENSI MANAJEMEN KONFLIK MELALUI PELATIHAN KOMUNIKASI ANTARBUDAYA BAGI PEGIAT KOMUNITAS PERDAMAIAN - Ayu Mawarti, Rista (Jurnal Praksis dan Dedikasi Sosial, 2022)
This study aims to analyze a series of efforts to improve the conflict management competence of peace activists through intercultural communication training. The main partners in this activity are the DNE Community and Gusdurian Malang City. The approach used in this service activity is the participatory and community development design which combines the involvement of the service team in training activities and evaluative analysis of the results. The results of the analysis of the implementation of activities show that: 1) planning and implementation of offline training is carried out with good coordination even in a ppkm situation; 2) the activity can be said to have succeeded in achieving its objectives, which can be seen through the enthusiasm of the participants in participating in the activity and 85 percent of the participants experienced an increase in conflict management competence, while the other 15 percent still needed further assistance; and 3) training activities have the potential to become a medium for further civic education learning in the community because of the requirements for internalizing national values in improving conflict management competencies. Kajian ini bertujuan untuk menganalisis serangkaian upaya peningkatan kompetensi manajemen konflik para pegiat perdamaian melalui pelatihan komunikasi antarbudaya. Mitra utama dalam kegiatan ini adalah Komunitas DNE dan Gusdurian Kota Malang. Pendekatan yang digunakan dalam kegiatan pengabdian ini yaitu desain participatory dan community development yang menggabungkan antara keterlibatan tim pengabdian dalam kegiatan pelatihan serta analisis evaluatif atas hasil yang ada. Hasil dari analisis pelaksanaan kegiatan menunjukkan bahwa: 1) Perencanaan dan pelaksanaan pelatihan secara luring dilakukan dengan koordinasi yang baik walaupun dalam situasi PPKM; 2) kegiatan dapat dikatakan berhasil mencapai tujuan yang tampak melalui antusiasme peserta dalam mengikuti kegiatan serta 85 persen peserta mengalami peningkatan kompetensi manajemen konflik, sementara 15 persen lainnya masih membutuhkan pendampingan lebih lanjut; dan 3) kegiatan pelatihan berpotensi menjadi media pembelajaran Pendidikan Kewarganegaraan lanjutan di masyarakat karena syarat akan internalisasi nilai-nilai kebangsaan dalam meningkatkan kompetensi manajemen konflik.